Evaluation of cyclic fatigue resistance of modern Nickel-Titanium rotary instruments with continuous rotation - Massimo Amato; Giuseppe Pantaleo; Dina Abdellatif; Andrea Blasi; Roberto Lo Giudice; Alfredo Iandolo (Ariesdue, 2017)
Aim: The aim of present study was to compare cyclic fatigue resistance of three modern Ni-Ti instruments used with continuous rotation. Materials and methods: For this study 3 groups of rotating instruments with continuous rotation (HyFlex EDM, Twisted File Adaptive, Revo S SU) have been used, each group consisted of 20 files. The various groups were subjected to cyclic fatigue testing through an artificial metal device. A statistical analysis with Kruskal-Wallis test and Mann-Whitney test was performed. Results: There were statistically significant differences between the three groups. The HyFlex EDM instruments have a fracture resistance slightly higher than the Twisted file and far higher than Revo S SU. Conclusions: Modern Ni-Ti alloys increase resistance of the rotating instruments to cyclic fatigue.